Investigating communication strategies in L2 learners’ discourse: a study in primary education - Papadopoulos, Isaak; Tzamali, Dimitra (Advances in Social Sciences Research Journal, 2015)
In cases of language learners’ inability to use a word/phrase in the target language, they opt for communication strategies by imitating sounds, inventing new words or using their hands to communicate. Although communication strategies are used very often by students, teachers are not fully aware of their importance during the teaching process and thus they do not train their students to use them. The aim of this study is to evaluate the use of communication strategies by learners of Greek as a second language during the lessons so that it can become obvious to teachers who abandon the message convey or switch to the first language to avoid miscommunication. The researchers used three methodological tools: (1) audio-recordings of naturally occurring classroom interactions and (2) observation notes taken in 25 class sessions. For the interaction transcripts, the researchers used the taxonomy of communication strategies of Faerch and Kasper’s (1983) while the researcher’s journal was used for the observations. The analysis of the results indicated that the most frequently used strategy used by the students was the language switch while the role of the teacher and the activities implemented each time were crucial as for the communication strategies used by the students.